Հայոց պատմությունը և վիպական բանահյուսությունը - Պետրոսյան, Արմեն («Նաիրի» հրատ.)
When there is no writing and written history, people record their history through epic compositions. But after the emergence of writing, the Armenian mind continued developing epics presenting historical eras. It might be said that the whole history of Armenia was codified through successive epics. In this article the following epic compositions are considered: 1) Ethnogonic legends; 2) ―Vipasank‖; 3) ―War of Persia‖; 4) ―War of Taron‖; 5) ―Daredevils of Sasun‖; 6) Kyoroghli; 7) Haiduk songs, and 8) Poems about the Soviet leaders.
Keywords: Բանահյուսություն